How ibrahim(as) came to know Allah: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story narrates the journey of Prophet Ibrahim as he seeks the truth about his Creator. Through observation of nature and reflection on the world around him, he realizes the oneness of Allah, emphasizing the importance of questioning and understanding one's faith.